2014
DOI: 10.1515/humor-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

On sarcasm, social awareness, and gender

Abstract: Sarcastic irony, uttered in four (within and between) gender-based settings, is used here as a tool to diagnose affective attitudes toward women. The kind of sarcasm tested here is an aggressive type of humor, whereby a speaker derides another individual, turning her or him into the victim of the humorous utterance. Finding this kind of irony less or more pleasing allows indexing between-and within-group attitudes. Participants were overall nonsexist, scoring low on sexism scales, but male participants were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Sarcasm directs a critical or humorous attitude at a specific target, sometimes resulting in ridicule or mockery (Glenwright & Pexman, 2010; Lee & Katz, 1998). As a communicative style, it serves various social purposes, such as softening a critical attitude (Dews & Winner, 1995), peppering humor into a conversation and maintaining a relationship (Dews, Kaplan, & Winner, 1995; Pexman & Olineck, 2002), or expressing power (Drucker, Fein, Bergerbest, & Giora, 2014). Sarcasm may also be used to reinforce one’s social identity, aggrandize out-group hostility, and foster intergroup competition (Burgers, Beukeboom, Kelder, & Peeters, 2015).…”
Section: Sarcasm and Potential Underlying Processesmentioning
confidence: 99%
“…Sarcasm directs a critical or humorous attitude at a specific target, sometimes resulting in ridicule or mockery (Glenwright & Pexman, 2010; Lee & Katz, 1998). As a communicative style, it serves various social purposes, such as softening a critical attitude (Dews & Winner, 1995), peppering humor into a conversation and maintaining a relationship (Dews, Kaplan, & Winner, 1995; Pexman & Olineck, 2002), or expressing power (Drucker, Fein, Bergerbest, & Giora, 2014). Sarcasm may also be used to reinforce one’s social identity, aggrandize out-group hostility, and foster intergroup competition (Burgers, Beukeboom, Kelder, & Peeters, 2015).…”
Section: Sarcasm and Potential Underlying Processesmentioning
confidence: 99%
“…Research has shown that males and females’ usage of nonliteral language differs. Males not only use irony and sarcasm more (e.g., Colston & Lee, 2004; Gibbs, 2000), they also report enjoying using sarcasm more than females (Drucker, Gergerbest, & Giora, 2014). Furthermore, differences between girls and boys in terms of social cognitive development have been found in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…These differential gender results may reflect an important role that verbal irony comprehension ability may play in male relationships. There is research in the adult literature to suggest that men enjoy sarcastic humour more than women and that both genders prefer sarcasm that is directed at men (Drucker et al, ). Gibbs () also found that men endorse making more sarcastic remarks than do women, which matches general perceptions that men are more likely to make ironic statements (Colston & Lee, ) as well as recent findings that school‐aged boys indicate more willingness to use sarcasm (Mewhort‐Buist et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although past work has not found gender differences in comprehension (Harris & Pexman, 2003), school-aged boys endorse more willingness to use sarcasm than do girls (Mewhort-Buist, Nilsen, & Bowman-Smith, 2018). Certainly, for adults, men enjoy sarcastic humour more than women and endorse using this language form more often than women (Drucker, Fein, Bergerbest, & Giora, 2014;Gibbs, 2000;Martin, Puhlik-Doris, Larsen, Gray, & Weir, 2003).…”
mentioning
confidence: 99%